Resistência ao Thrips tabaci: avaliação em acessos de cebola e em ciclos de seleção recorrente na ‘BRS ALFA São Francisco’ - Ferreira, Glêyce de Oliveira (2016)
The Brazilian onion cultivation has significant commercial importance and strong social connotation, because it involves small farmers, most of them belonging to the family nucleus. In the Northeast of Brazil, its cultivation is carried out during the entire year, generating around 60 thousand direct and indirect jobs. Onion crops are vulnerable to diseases and pests, such as Thrips tabaci, major pest affecting these crops, causing damages above 50%. The species Allium cepa presents wide phenotypic variability, allowing the creation of new cultivars for various conditions and requirements. This study aimed to evaluate onion accessions regarding its resistance to T. tabaci, in order to enable the development of cultivars that are resistent to this pest. The experiments were conducted in randomized block design with three replications on the experimental fields at Embrapa Semiárido, situated in the municipalities of Petrolina/PE and Juazeiro/BA. The results achieved concerning the degree of infestation (DI) in percentage for nymphs and adults were transformed into arc sine of the square root for statistical analysis. Plant architecture traits, bulb productivity and estimated simple correlations among all variables were also evaluated. Five evaluations of thrips populations were carried out after transplanting, each one after seven days. Statistical differences were observed for a number of adults to different evaluations, while the number of nymphs showed no statistical differences. The largest average productions of commercial bulbs were observed for the TX08, IPA 11, Alfa SF C-IX, IPA 10 and Sirius F1 acessions while the Red Creole, Creole Mercosur and Conquest acessions had the lowest productions. The commercial productivity of bulbs had simple negative correlations with nymph DIs in the five phases of evaluations and adult GIs within 22 (n22a) days. Negative correlations between productivity of commercial bulbs x central angle of the plant were observed, indicating that plants with higher bulb production have lower angle on the central leaves. The results of the study show that the resistance mechanism is antixenosis associated with the tolerance mechanism.